2005
DOI: 10.1074/jbc.m412594200
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal CCA-adding Enzymes

Abstract: The CCA-adding enzyme (tRNA nucleotidyltransferase) builds and repairs the 3 end of tRNA. A single active site adds both CTP and ATP, but the enzyme has no nucleic acid template, and tRNA does not translocate or rotate during C75 and A76 addition. We modeled the structure of the class I archaeal Sulfolobus shibatae CCA-adding enzyme on eukaryotic poly(A) polymerase and mutated residues in the vicinity of the active site. We found mutations that specifically affected C74, C75, or A76 addition, as well as mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 52 publications
(110 reference statements)
3
35
0
Order By: Relevance
“…Both enzymes contain β-turn structures close to the active site and sequence motifs located on these β-turns seem to be specific for CCA or poly(A) addition [38,39]. It was also demonstrated that in CCAtrs the tRNA precursor substrate does not translocate during CCA synthesis: If the tRNA was cross-linked to the enzyme CCA was still faithfully added to the tRNA's 3′ end [61].…”
Section: Primer Substrate Recognition and Processivitymentioning
confidence: 92%
See 1 more Smart Citation
“…Both enzymes contain β-turn structures close to the active site and sequence motifs located on these β-turns seem to be specific for CCA or poly(A) addition [38,39]. It was also demonstrated that in CCAtrs the tRNA precursor substrate does not translocate during CCA synthesis: If the tRNA was cross-linked to the enzyme CCA was still faithfully added to the tRNA's 3′ end [61].…”
Section: Primer Substrate Recognition and Processivitymentioning
confidence: 92%
“…Part of the ribonucleoprotein template pocket consists of a conserved β-turn structure which is structurally and functionally conserved in all CCAtrs [38]. A variant of this structure is also found in the bacterial PAPs where it is most likely involved in primer recognition and thus far is the only motif found to distinguish class II CCAtrs and PAPs [39].…”
Section: Structure Of Active Sites In Cca-adding Enzymesmentioning
confidence: 99%
“…Unlike poly(A) polymerases, CCA-adding enzymes not only add two different nucleotides in a defined order but terminate addition after three nucleotides (1,12,14). The cocrystal structures of two class II enzymes [the BstCCA enzyme in complex with CTP or ATP (14) and the A. aeolicus class II A-adding enzyme in complex with tRNA-NCC and a nonreactive ATP analog (21)] suggest that three residues in helix J (R194, M197, and E198) may constrain the growing 3Ј end of tRNA and/or help to thread it into the active site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other protocols (mutagenesis, protein expression, preparation of RNA substrates, and enzyme assays) have been described previously (12,22), and details are available upon request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation